Hierarchical process model discovery algorithm for CRS systems - Stroiński, Andrzej; Dwornikowski, Dariusz; Kobusińska, Anna; Brzeziński, Jerzy (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
An increasing number of distributed systems are currently being developed according to the REST paradigm, supporting a diverse range of services and applications. However, analyzing potential errors and deviations in their operation has become progressively more difficult due to both the scale of processed data and the proliferation of available services. In this context, process mining offers a valuable approach. By analyzing event logs collected from such systems, it is possible to derive process models that represent application behavior in distributed environments. These models support the identification and remediation of errors as well as the optimization of system performance. This article introduces a mechanism for representing process models of communication resource systems (CRS) developed within the REST paradigm using process algebra. In addition, we propose an algorithm for discovering such models, enabling the identification of both local processes executed within individual services and the interactions that occur between them.